Khidmah Sebagai Experiential Learning dalam Pembentukan Resiliensi dan Jiwa Kewirausahaan Mahasiswa Prodi Psikologi di Universitas Islam Tribakti - Zaenab Niswati Kamali; Moh. Irmawan Jauhari; Nila Ainu Ningrum (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the role of khidmah as a form of experiential learning in developing resilience and an entrepreneurial spirit. The research method uses a case study approach through observation, in-depth interviews, and documentation analysis in the context of Islamic boarding schools. The results show that khidmah contributes significantly to the formation of resilience by strengthening the values of responsibility, discipline, independence, integrity, and adaptability. In addition, the practice of khidmah in managing Islamic boarding school business units also serves as an effective learning space for entrepreneurship, training managerial skills, creativity, decision-making, and collaboration. Thus, khidmah is not only a means of forming religious character, but also a holistic learning model that strengthens mental toughness and fosters an entrepreneurial spirit based on spiritual and social values.